Receita de contrato com cliente (IFRS 15 / CPC 47): aspectos contábeis do segmento de medicina diagnóstica no Brasil - Aquino, Carlos Elder Maciel de (2019)
The International Accounting Standards Board (IASB) and the Financial Accounting Standards Board (FASB) joined in 2010 in favor of a project to treat revenue from contracts with customers, given the need to harmonize the criteria for recognition and disclosure of information to stakeholders. The IASB issued in 2014, effective as from 2018, IFRS 15 - Revenue from Contracts with Customers, regulated in Brazil through CPC 47. This research, characterized as exploratory, bibliographical, documentary and qualitative and descriptive in relation to the approach of the problem, sought to particularize the verification of adherence to these standards by companies in the segment of diagnostic medicine in Brazil. Recognizing revenue and disclosing it adequately is a challenge for this segment, given the nature of its service contracts, for involving health plans, government, insurance, hospitals and others, as well as for the possibility of a service glosses. It was concluded that there is much to be done in terms of standardization, completeness and transparency of the information disclosed to financial statements users. Thus, users lose because they do not have enough and explanatory information for their economic decision-making and lose the companies in the segment, because, with the current model of disclosure, it makes it difficult to attract new investors, hindering and / or expensive access to national and international capital markets. For future research it is suggested to broaden the understanding of the diagnostic medicine segment's revenue cycle, exploring, for example, the methodology for calculating the estimation bad debts expense and the allowance for doubtful accounts and its accounting, as well as applying this study to other segments of the health sector, such as hospitals and private health insurers